Perturbed Nuptiality, Delayed Fertility: Childbirth Effects of Covid19 - Mazhar Mughal; Rashid Javed (Global Labor Organization (GLO), 2021)
An aspect of the Covid-19 pandemic that merits attention is its effects on marriage and childbirth. Although the direct fertility effects of peo- ple getting the virus may be minor, the impact of delayed marriages due to the first preventive lockdown, such as that imposed in Pakistan from March 14 to May 8 2020, and the closure of marriage halls that lasted till September 14 may be non-negligible. These demographic consequences are of particular import to developing countries such as Pakistan where birth rates remain high, marriage is nearly universal, and almost all child- bearing takes place within marriage. Based on historic marriage patterns, we estimate that the delay in nuptiality during the first phase of coron- avirus outbreak may affect about half of the marriages that were to take place during the year. In Pakistan, childbearing begins soon after mar- riage, and about 37% of Pakistani married women give birth to their first child within twelve months of marriage. A sizeable number out of these around 400,000 annual births that occur within twelve months of the mar- riage may consequently be delayed. Postponement of marriages due to the accompanying difficult economic situation and employment precari- ousness should accentuate this fertility effect. The net fertility impact of the Covid-19 outbreak would ultimately depend not only on the delay in marriages but also on the reproductive behavior of existing couples.
Keywords: I10; I18; J10; J12; J13; 330; COVID-19; coronavirus; lockdown; marriage; childbirth; fertility; Pakistan